Implementing Discovery Learning Model using Virtual Laboratory: An Insight to Differentiation Learning Strategies - Arina Zaida Ilma; Afit Istiandaru; Nunik Sri Ritasari (Jurnal Penelitian Pendidikan IPA, 2024)
Students have unique and diverse characteristics. One of the strategies used to facilitate student diversity is through differentiation learning. The research aims to explain the findings or problems of case studies in learning Physics at SMAN 8 Yogyakarta and explain the differentiated learning to solve these problems. The research approach used is qualitative with the case study method. Data collection techniques use non-test techniques using documentation and observation. Based on the results, differentiated learning can facilitate the needs of students who have diverse learning modalities, including students with visual and kinesthetic learning modalities. The implementation of discovery learning using virtual laboratories assisted by PhET Colorado can be an alternative learning model in teaching Physics. Future research can measure students' knowledge, attitudes or skills in applying differentiated learning and combining it with other learning models